2019
DOI: 10.15406/ijh.2019.03.00179
|View full text |Cite
|
Sign up to set email alerts
|

Land use dynamics in the context of variations in hydrological regimes in the upper Senegal River basin

Abstract: The objective of this study is to analisis the climatic vulnerability of water resources in the Senegal iver and Gambia basins. The study concerns the analysis of rainfall data, flow rates of Modis-Terra satellite images. Time series of study data are variable. The purpose of this study is to analysis climate vulnerability on water resources in the Senegal River and Gambia basins. It is based on the exploitation, on the one hand, of the chronicles of annual rainfall amounts and annual flows of the tributaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…The three other studies simulated the surface runoff (SURQ) in different sub-catchments of SRB during recent periods. The results of the two studies carried out by Faty et al (2019) and Sun et al (2013) showed comparable surface runoff values with our study. Furthermore, the above mentioned three studies were carried out in small catchments in SRB, while in our study the SURQ was estimated for the whole SRB.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
See 2 more Smart Citations
“…The three other studies simulated the surface runoff (SURQ) in different sub-catchments of SRB during recent periods. The results of the two studies carried out by Faty et al (2019) and Sun et al (2013) showed comparable surface runoff values with our study. Furthermore, the above mentioned three studies were carried out in small catchments in SRB, while in our study the SURQ was estimated for the whole SRB.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
“…This evidence emerged in the three watersheds. Similar result was also reported by Faty et al (2019), particularly in the upper reach of SRB. This decrease in SURQ was also noted by Mahmood and Jia (2019) in the LCB.…”
Section: Assessment Of Combined and Separate Impacts Of Lulc Changes ...supporting
confidence: 90%
See 1 more Smart Citation
“…26 In Senegal and The Gambia, the rainfall deficit was estimated at 10%, in West Africa it reaches 20% to 25%, affected by droughts and land use, evidencing the need to consider climatic variables in the management of water resources. 27 In Bahia, a state in northeastern Brazil, a downward trend in rainfall in the historical series was also identified, indicating a change in the water pattern. 28 The study is replicable to other risk areas in Brazil and Latin America, where similar situations occur due to the climate variation.…”
Section: Discussionmentioning
confidence: 91%